Pengaruh Pendidikan, Pengangguran, Kesehatan, Ketimpangan Pendapatan, dan Upah terhadap Kemiskinan di Kabupaten/Kota Provinsi Sumatera Barat - Noviatus soliha (CERED Indonesia Institute, 2023)
This study aims to determine the effect of education, unemployment, health, income inequality, and wages on poverty in districts/cities of West Sumatra province, as well as the effects of education, unemployment, health, income inequality, and wages together on poverty in districts/cities of West Sumatra province. This study uses secondary data for the last six years, namely 2017-2022. The study uses research objects in the districts/cities of West Sumatra Province which consist of 19 regencies/cities. This research shows that: 1) Education has a positive and insignificant effect on poverty in the districts/cities of West Sumatra Province 2) Unemployment has a positive and insignificant effect on poverty in the districts/cities of West Sumatra Province 3) Health has a negative and significant effect on poverty in the districts/cities of West Sumatra Province 4) Income inequality has a positive and insignificant effect on poverty in the Regencies/Cities of West Sumatra Province 5) Wages have a negative and insignificant effect on poverty in the Regencies/Cities of West Sumatra Province 6) Education, unemployment, health, income inequality, and wages together the same significant effect on poverty in the Districts/Cities of West Sumatra Province.